Linear inequalities concerning partitions into distinct parts - Merca, Mircea (The Ramanujan journal, 2022)
Linear inequalities involving Euler’s partition function p ( n ) have been the subject of recent studies. In this article, we consider the partition function Q ( n ) counting the partitions of n into distinct parts. Using truncated theta series, we provide four infinite families of linear inequalities for Q ( n ) and partition theoretic interpretations for these results.